Analisis Implementasi Akuntansi Manajemen sebagai Pendorong Budaya Inovasi Digital dalam Meningkatkan Daya Saing pada PT Unilever Indonesia Tbk. 2024 - Aninda Nuraini; Anis Fitriyani; Chania Cahayaningrum; Ibnu Wahyuda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Rapid technological developments are driving companies to transform and build an innovation-oriented work culture in order to maintain competitiveness. Management accounting plays an important role as a strategic information system that provides accurate data for management in formulating policies, improving efficiency, and encouraging digital innovation. This study aims to analyze the application of management accounting at PT Unilever Indonesia Tbk. as a driver for the formation of a digital innovation culture and increased company competitiveness in 2024. This study uses a qualitative approach with a descriptive method based on secondary data from interim financial reports and company documentation. The results show that the implementation of digital management accounting through the integration of ERP systems, IoT-based UMS, and the use of artificial intelligence (AI) contributes to increased operational efficiency and cost control. Despite a decline in sales and gross profit, the company managed to increase its net profit by 2.84% through administrative cost savings. Digital management accounting serves as a strategic partner in decision-making and forms the foundation for a culture of innovation. Its implementation also supports the three dimensions of Dynamic Capabilities theory, namely sensing, seizing, and transforming, which comprehensively strengthen the company's competitiveness and sustainability in the digital era. Thus, digital management accounting is not merely a recording tool, but a key strategic partner in driving innovation, enhancing competitive advantage, and ensuring business sustainability in the digital age.